Pericardium is removed, but the anasarca remains. Multidisciplinary management of constrictive pericarditis: a case report - Z. N. Sukmarova; L. A. Matskevich; E. Yu. Andreenko; S. A. Beregovskaya; O. B. Maksimova; E. P. Evseev; T. G. Nikityuk; O. M. Drapkina (Кардиоваскулярная терапия и профилактика)
A case of a 70-year-old male patient is presented, in whom constrictive-effusive pericarditis debuted after vaccination against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), and over the six months progressed in edema and ascites, refractory to therapy. A year later, after coronavirus disease 2019 (COVID-19), signs of increasing heart failure were noted, accompanied by an increase in proinflammatory markers, myocardial damage indicators. The diagnosis of constrictive-effusive pericarditis was made another 9 months later at the anasarca stage. The difficulties in diagnosis were that the pericardium remained non-thickened according to radiological methods. In addition, there were discrepancies in the data of computed tomography and echocardiography. Cardiac decortication was performed. However, within 2 months after the operation, no significant edema and ascites regression was achieved. In addition, the levels of inflammatory markers remained elevated, which was assessed as polyserositis. Anti-inflammatory therapy with anakinra and colchicine was prescribed with successful edema and ascites resolution within 2 months. The genetically engineered drug was gradually discontinued, and colchicine was continued for up to a year. During control examinations after 6, 12, and 18 months, no exacerbations were observed, and the NYHA heart failure class 1 remained. The patient receives minimal therapy, including eplerenone 25 mg, torasemide 5 mg, and atorvastatin 20 mg.Conclusion. The peculiarity of pericarditis course in this case is a rapidly progressing increase with unclear inflammatory manifestations, progression with repeated stimulation with viral antigens, rapid development of constriction without significant thickening of the pericardial leaflets. Persistent polyserositis can be the cause of therapy-resistant edema and ascites in patients after pericardiectomy. The possibility of torpid inflammation in patients with edema and ascites should be taken into account.